Rare Association Between Pernicious Anemia and Neurogenic Bladder A Case Report and Literature Review (Journal of Medicine, 2014)
Pernicious anemia is the most common cause of vitamin B12 deficiency, being characterized by destruction of the gastric mucosa and the presence of auto-antibodies. We describe a rare case of neurogenic bladder associated with pernicious anemia. The neurologic manifestations (muscular weakness) were partially reversed with vitamin B12 replacement, but the vesical symptoms persisted. It is important to investigate the presence of vitamin B12 deficiency in cases of neurogenic bladder.DOI: http://dx.doi.org/10.3329/jom.v15i1.19883 J Medicine 2014; 15: 87-90